IMPROVING STUDENTS’ SPEAKING THROUGH THE USE OF EDUCATIVE CARTOON FILM - Arisca, Nadya; Sutapa, Gatot; Riyanti, Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this research was to know how educative cartoon film improved students’ speaking at the tenth grade students of MAN 2 Pontianak in academic year 2017/2018. The research was conducted with Classroom Action Research in two cycles. The subject of this research was 38 students in class X MIPA 4. The researcher used observational checklists, field notes, and speaking performance as tools to collect the data. The result showed that the use of educative cartoon film improved students’ speaking. Based on the observational checklists and field notes, it showed that the students and the teacher’s behavior changed during the teaching and learning process that caused the students to be more enthusiastic and focus in teaching and learning activity. Furthermore, from the speaking performance, the students did not stutter anymore and displayed less tension while performing their speaking in front of the class. As the result, the researcher recommends the teacher in high school settings to use educative cartoon film as teaching media to teach speaking in order to help students focus and improve their speaking. Keywords: Educative Cartoon Film, Speaking